Optimizing predictive accuracy of the two-component repair model for pediatric TBI: Pediatric-specific parameters, toxicity endpoint harmonization, and dose-rate safeguards - Ruijie Meng (Clinical and Translational Radiation Oncology)
In response to the innovative two-component repair model for pediatric TBI renal toxicity prediction, this letter proposes three key refinements to enhance clinical translation: adopting pediatric-specific radiobiological parameters (e.g., DNA-PKcs dynamics, α/β ratios) to address systematic overestimation of radiation tolerance; harmonizing toxicity endpoints to CTCAE v5.0 ≥Grade 3 criteria to strengthen doseresponse associations and enable precise risk stratification; and implementing institution-specific minimum dose-rate thresholds to mitigate unmodeled vascular susceptibility during low-dose-rate TBI. Collectively, these optimizations will improve predictive accuracy and support personalized radiotherapy for high-risk pediatric cohorts.